IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DALAM PKN UNTUK MENUMBUHKAN TOLERANSI DAN NASIONALISME SISWA SEKOLAH DASAR - Dwi Nurmansyah; Muhammad Fauzan Muttaqin (JISPE Journal of Islamic Primary Education, 2024)
Multicultural education has an important role in shaping the character of students who are tolerant, inclusive, and nationalistic, especially in Indonesia, which has a rich diversity of cultures, religions, and languages. This study aims to explore the application of multicultural education in Civic Education (Civics Education) subjects at the SD/MI level as a step to foster a sense of nationalism in students. Using a qualitative approach and descriptive method, data were collected through interviews, observations, and documentation studies at MI Mathlaulhuda Parung Panjang in November 2024. The results showed that multicultural education in Civics helps students understand the importance of tolerance and diversity, which is reinforced through various strategies such as discussions, assignments, and project-based activities. Challenges faced include limited learning resources and a lack of specialized training for teachers. Nevertheless, efforts to integrate multicultural values through the Pancasila Student Profile Strengthening Project (P5) succeeded in improving students' understanding of unity in diversity. This research emphasizes the importance of multicultural education as a preventive measure to create a young generation that appreciates diversity and contributes to the harmony of the nation